Computer sciences student competency system (CSSCS) for intelligent system engineering (CS223) - Hassan, Norhazira (2013)
This research is conducted in order to develop an information system that will close the gap of industry demands and university supplies by mapping the computer sciences student skills needed by industry and supply provided by the university with the job opportunities. For this project, the developer’s team consists of 9 persons. Each of them will be responsible for the same system but in different scope. For this research, it will focus on developing the Computer Sciences Student Competency System (CSSCS) for Computer Science programs of Faculty of Computer Science and Mathematics in UiTM Shah Alam for Bachelor of Information Technology (Hons) Intelligent System Engineering (CS223) program. For the project aim, by using the standard that UiTM already have, and then comparing it with the market needs, the project will come out with the suitable competencies on how to measure students’ performance in industrial training based on their technical skill. This system also aims to help the supervisor to evaluating the student for industrial training. Other than that, it also focuses on identifying the skill needed in industry and what the criteria that industry need from candidates in Science Computer field for particular job. It also helps the student to know what job that suitable for their own skills.